2015
DOI: 10.4103/1119-3077.158976
|View full text |Cite
|
Sign up to set email alerts
|

Temperature increases on the external root surface during endodontic treatment using single file systems

Abstract: The single file rotary systems used in this study may be recommended for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Temperature alterations transmitted to the root surface may be harmful to the surrounding tissues, because the heat generated inside the canal dissipates through dentine, reaching the cementum, periodontal ligament and alveolar bone [25]. Some histological aspects may explain the data presented in this work and corroborate the findings of others reports [25,26]. In this study, the evaluation of dental pulp conditions (after harvest by rotary and manual techniques) was evaluated by histological analyses, which do not consider immunohistochemistry features.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Temperature alterations transmitted to the root surface may be harmful to the surrounding tissues, because the heat generated inside the canal dissipates through dentine, reaching the cementum, periodontal ligament and alveolar bone [25]. Some histological aspects may explain the data presented in this work and corroborate the findings of others reports [25,26]. In this study, the evaluation of dental pulp conditions (after harvest by rotary and manual techniques) was evaluated by histological analyses, which do not consider immunohistochemistry features.…”
Section: Discussionsupporting
confidence: 75%
“…In the manual instrumentation group structures of pulp were well-preserved, the preservation of the vascular and nervous architecture, as well as the cellularity in the central region. Despite this, studies that showed the clinical use of rotary nickel-titanium (NiTi) endodontic instruments improves the efficiency of endodontic treatment by reducing the time spent on treatment procedures, sensitivity and complication risks [26].…”
Section: Discussionmentioning
confidence: 99%